Information Technology and Russia's Social Modernization - Svetlana Petukhova; Margarita Strepetova (International Telecommunications Society (ITS), 2010)
Information technologies play a very important role in modernizing Russia's economy and society as whole. Its competitive advantage lies in the availability of highly educated labour resources. Russia accounts for approximately 9% of researchers in the world as opposed to a share of about 0.3% in the world innovation market. Our approach is based on identifying ways to set up IT innovation centres and create an organizational and economic mechanisms making possible the transfer of new technologies to production processes and the creation of tools for innovative management. In the markets of high technology Russia will concentratie on software tools for IT security, applied modelling information systems, various types of software, and cryptographic systems, some types of specialized computing systems. In the Education Project two main mechanisms of systemic change are envisaged: to identify and support leading higher educational institutions; to introduce on a grand scale new knowledge-management methods and put mechanisms into practice. Among the main intentions of the Education Project the following should be mentioned: the modernization of its material-technical base, the internetization of education, the expansion of innovation centres on the pattern of universities and scientific and research institutes, the creation of Russian "Siliceous Valley"- Skolkovo complementary clusters of small, innovative companies. In the framework of the Health Care 2020 Programme. Activities are underway to introduce a Federal Register of the most widespread diseases, to operate waiting lists of those who need high technology medical help, and to centralize access to the common database of normative and reference information. Drafts of their electronic presentation formats are developed on the basis of international ISO standards. An Internet market for various types of medical and information services is being set up; telemedicine technologies are being taken into account. The social orientation of IT development will improve educational and health care systems, accelerate progress in extending the number of qualified professionals in IT (according to experts, the demand for these in 2012 will increase by up to 550,000 persons, and even then the country's demand will only be satisfied to the degree of 15%). A model enabling Russia to enter the group of countries with a high development of intellectual potential demands more intensive introduction of IT in modernization of Russian society.
Keywords: F0; O3; D83; 330; codes Information technology; human factor; modern economy; social factors; telecommunication; education; personal training; medicine; national healthcare; telemedicine; social networks; internatization